Fecal immunochemical test for hemoglobin in combination with fecal transferrin in colorectal cancer screening - Gies, Anton; Cuk, Katarina; Schrotz-King, Petra; Brenner, Hermann (United european gastroenterology journal, 2018)
Objective - Fecal transferrin has been suggested as a complementary or even superior marker for early detection of colorectal cancer (CRC) besides fecal hemoglobin. We aimed to evaluate both markers individually and in combination in a large cohort of participants of screening colonoscopy. - Methods - Precolonoscopy stool samples were obtained from participants of screening colonoscopy and frozen at −80℃ until blinded analysis, using a dual-quantitative fecal immunochemical test (FIT) for hemoglobin and transferrin. Sensitivity, specificity and area under the curve (AUC) were calculated for CRC and advanced adenoma (AA). - Results - A total of 1667 participants fulfilled our inclusion criteria. All individuals with advanced neoplasm (AN) (16 CRC, 200 AA) and 300 randomly selected participants without AN were included. Mean age was 63 years and 56% were male. The AUC for CRC and AA was 92% and 68%, respectively, for hemoglobin vs. 79% and 58%, respectively for transferrin. Combination of both markers yielded an AUC for CRC and AA of 92% and 68%, respectively. - Conclusion - FIT for hemoglobin shows better diagnostic performance than FIT for transferrin for the detection of ANs (both proximal and distal neoplasms), and a combination of both markers does not improve the diagnostic performance.